A Place to Live and to Die: A Qualitative Exploration of the Social Practices and Rituals of Death in Residential Aged Care. (May 2022) - Balmer, D. G.; Frey, R.; Gott, M.; Collier, A.; Boyd, M.
In many countries, an increasing proportion of deaths occur in residential aged care (RAC) (nursing homes) meaning that these have become both a place to live - a home- and a place to die. This paper reports on death practices and rituals in 49 RAC facilities in Aotearoa/New Zealand narrated in semi-structured interviews with staff. Themes coalesced around 'good death'. Dying alone was not seen as a good death and the demands of trying to prevent this caused tension for staff. Meeting family wishes, post death decision-making, after death practices and rituals, including communicating and remembrance of the death, were explored as part of good death. Overall, death rituals in RAC were limited. Balancing the needs of the living, the dying and the dead created tension. The rituals and practices facilities are currently enacting in death/post-death require attention, since more people will die in RAC with increasingly diverse needs.